2011
DOI: 10.1021/ma102529f
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Charge-Carrier Mobility in High-Pressure-Crystallized Poly(3-hexylthiophene)

Abstract: b S Supporting Information P olymeric organic semiconductors, like many other macromolecular systems, can display the full spectrum of microstructures, from essentially disordered, or amorphous, to highly crystalline. Many electronic properties and processes are critically depending on this molecular and supramolecular order. [1][2][3][4] However, it often is still unclear which particular microstructural aspects contribute to the macroscopic electronic attributes of these materials. In the field of commodity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 30 publications
2
58
1
Order By: Relevance
“…From the charge transport viewpoint, one important issue remains the possibility to crystallize high-M w P3ATs in the form of extended-chain crystalline domains, trying to reduce the level of amorphous material and promoting long range crystalline perfection. Some preliminary studies in that direction have been reported recently 95 suggesting that high-pressure crystallization of P3HT may lead to higher charge carrier mobilities. Further improvements can be foreseen with mastering of chemical defects in the chains of P3Ats.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…From the charge transport viewpoint, one important issue remains the possibility to crystallize high-M w P3ATs in the form of extended-chain crystalline domains, trying to reduce the level of amorphous material and promoting long range crystalline perfection. Some preliminary studies in that direction have been reported recently 95 suggesting that high-pressure crystallization of P3HT may lead to higher charge carrier mobilities. Further improvements can be foreseen with mastering of chemical defects in the chains of P3Ats.…”
Section: Discussionmentioning
confidence: 96%
“…[92][93][94][95] Correlations between the molecular structure of the monomeric units made of several chemical moities and the crystalline packing in the unit cells (especially the p-p-stacking) need still to be established. In this perspective, P3HT is certainly a case system to test the applicability of experimental methods and insights gained when investigating conventional polymer crystallization, for example, using epitaxial crystallization methods, self-seeding or nucleating agents.…”
Section: Discussionmentioning
confidence: 99%
“…The relative contribution of molecularly ordered and disordered regions to transport is manipulated using different thermal treatments, resulting in different degrees of energetic disorder within FETs and thus in a strong modulation of the thermal barriers to electron transport. A transport improvement with lamellar thickening, obtained upon annealing at T2, is generally expected in semicrystalline polymers, 62 but it has been rarely demonstrated, 63,64 especially in solution processed films and FET architectures. Owing to the retention of backbone orientation upon annealing at T2, energetic barriers for charge transfer are strongly reduced exclusively in the direction of chain alignment, where effective interconnectivity of ordered regions can be more easily gained, leading to temperature-independent electron transport near to 300 K. In contrast, in the direction perpendicular to the backbone, thermal charge transport barriers are independent whether the material is annealed at T1 or T2, which is not surprising as in the -stacking direction coherence length is much smaller in any case.…”
Section: Discussionmentioning
confidence: 99%
“…Arguably, melt‐processing is free from all the drawbacks previously mentioned for solution processing, yet nearly all the benefits are preserved. Stingelin‐Stutzmann and co‐workers have performed extensive studies on melting poly(3‐hexylthiophenes) and small molecule organic semiconductors . The adoption of melt‐processing for organic electronics is however further complicated by the fact that almost all high performance donor–acceptor‐based semiconducting polymers exhibit high melting temperatures (i.e., >250 °C) or decompose before they melt.…”
mentioning
confidence: 99%